China/Russia 2030 : Implications for the Horticulture Sector in Central Asia - World Bank (World Bank, Washington, DC, 2019)
In China, changing demographics, rising incomes and shifting consumer preferences have resulted in an ever-growing demand for food that is more varied, healthier and of higher quality and this demand is set to persist well into the future. According to International Monetary Fund projections (2019), by 2024, Chinese per capita gross domestic product (GDP, in current prices) will increase to dollar 28,450, from dollar 13,130 in 2019, and the population will increase to 1.5 billion people (United Nations, 2019). The projected urbanization rate will reach 67 percent by 2030, compared to 56 percent in 2015 (Goh et al., 2014). The growing number of consumers in China, that are increasingly more affluent and educated, will continue shifting their dietary preferences to include more protein, fruits and vegetables. Central Asian countries are well placed to be more competitive in satisfying fruit import demand in the growing Chinese markets and will reap economic and social development benefits along the way. For centuries, Central Asia has occupied a position of strategic importance in trade between the East and the West. The region’s geographic location, natural resources, untapped yield potential, and the possibility of greater private sector investment through policy reform create the necessary preconditions for the Central Asian countries to increase their agricultural exports to China. As China places an important role on meeting its growing food needs on dynamic agricultural trade and investment cooperation with the Central Asian countries, this results in significant opportunities for the region to increase its presence in the Chinese fruit markets brought by improved infrastructure and higher cross-border investment. For example, according to the recent World Bank report (World Bank, 2019), Belt and Road Initiative transport projects are estimated to increase trade by up to 9.7 percent. Countries that have a comparative advantage in time-sensitive sectors, such as fresh fruits and vegetables, are expected to be the biggest winners.